Soil-structure interaction effects on the seismic collapse capacity of steel moment-resisting frame buildings. (August 2021) - Hamidia, Mohammadjavad; Shokrollahi, Nima; Nasrolahi, Maryam
Abstract: FEMA P695 proposes quantification of soil-structure effects as a field of research to adjust the collapse margin ratio. The Winkler foundation with elastic and inelastic stiffness is used to address interaction effects. Three-, nine- and 20-story steel moment-resisting frame buildings are selected, and the collapse margin ratio of the buildings for site classes C and D are evaluated. The nonlinear soil behavior leads mostly to an increase in seismic collapse probability compared to linear soil behavior and fixed-base conditions. Finally, simplified adjustment equations are proposed for estimating the collapse margin ratio of structures considering the soil-structure interaction effects.